Efektivitas Vaksin COVID-19 mRNA Booster Kedua pada Tenaga Kesehatan di Rumah Sakit Umum Pusat Nasional Dr. Cipto Mangunkusumo dan Faktor yang Memengaruhinya - Lubis, Siti Taqwa Fitria; Koesnoe, Sukamto; Yunihastuti, Evy; Shatri, Hamzah; Karjadi, Teguh Harjono; Harimurti, Kuntjoro; Pitoyo, Ceva Wicaksono; Yunir, Em (UI Scholars Hub, 2024)
Introduction. The emergence of the Omicron variant during the pandemic had an impact on the effectiveness of the COVID-19 vaccine. The spread of Omicron increased rapidly even in populations that had been vaccinated with booster doses, causing a high incidence of infection. This study aimed to determine the effectiveness and factors related to the effectiveness of the second mRNA booster vaccine as well as antibody levels after the second mRNA booster vaccine in healthcare workers at Cipto Mangunkusumo National General Hospital. Methods. This study used a cohort design. Total sampling of 271 healthcare workers were obtained from previous research and continued with consecutive sampling. Selected subjects were interviewed, and blood samples were taken to measure IgG sRBD antibody levels. The effectiveness of the vaccine was calculated, and bivariate and multivariate analysis was carried out to assess the factors that influenced the effectiveness of the second mRNA booster vaccine. Results. A total of 9 subjects (5.6%) were infected with COVID-19 in the second booster vaccine group and 11 subjects (9.7%) in the first vaccine group. The effectiveness of the vaccine against COVID-19 infection was 42% (CI 95% -37 – 75%), p = 0,215. Age, gender, hypertension, type 2 DM, obesity, smoking, and COVID-19 infection before booster have no relationship to the effectiveness of the second booster mRNA vaccine. In 48 subjects who had their antibody levels checked during the first and second boosters, there was an increase from 4,743 AU/ml (IQR 6,053.3) to 8,532 AU/ml (IQR 8,040.3). Conclusions. The effectiveness of the second mRNA booster vaccine against COVID-19 infection in healthcare workers was 42%. There were no factors related to the effectiveness of the second mRNA booster vaccine. The sRBD antibody levels after the second booster vaccine were higher than the first booster vaccine.